Effects of different operating conditions of air fryer and convection oven on the quality of moist chocolate cake - Mior Zakuan Azmi, Mazidah (2019)
Processing parameters in different operating conditions play important roles for producing a good-quality cake. Baking temperature, airflow velocity, and baking time are among the important processing parameters that influence heat transfer mechanisms in the operating conditions during baking process. The purpose of this study is to investigate the effect of processing parameters in different operating conditions of air fryer and convection oven on the quality of moist chocolate cake. The operating conditions: airflow rate (air fryer = 5.11 m/s and convection oven = 0.88 m/s), baking temperature (150 - 170 °C), and baking time (40 - 50 min). Oven temperature, cake temperature, and volume expansion were measured during the baking process. The optimum baking temperature and baking time were determined by using response surface methodology (RSM). Relative height, moisture content, texture, color, and overall acceptability of the cakes were analyzed. Fourier’s law model was used to describe the influence of baking temperature and baking time on the internal cake temperature during the baking process. The results showed that higher airflow rate significantly accelerated (p<0.05) the heating process, thus increased the convective heat transfer during baking. An increase in baking temperature with higher airflow produced higher surface cake temperature, internal cake temperature and higher expansion rate, (0.35 to 0.46 cm/min) during baking as compared to the convection oven-baked cake. During high baking temperature, the moisture content reduced by 14.3% using the air fryer and 14.5% using the convection oven. The optimum air fryer-baked cake at 150 °C for 25 min had higher relative height (37.19%), higher moisture content (28.80%), and lower crumb firmness and chewiness (5.05 N and 1.42 N, respectively), lower total color change (ΔE) (6.2) and most preferable in overall acceptance as compared to the convection oven-baked cake. The model of heat transfer on the internal cake temperature for the air fryer had an excellent correlation with the experimental data (R>0.9) and the maximum errors were less than 10%. Oven temperature profile, cake temperature profile, and volume expansion significantly influenced the baking process, which consequently affected the final cake quality. The use of the air fryer for baking cakes effectively reduced baking time by 40% as compared to the convection oven.